Proof by Cases/Formulation 2/Reverse Implication

From ProofWiki
Jump to navigation Jump to search


$\vdash \paren {\paren {p \lor q} \implies r} \implies \paren {\paren {p \implies r} \land \paren {q \implies r} }$


By the tableau method of natural deduction:

$\vdash \paren {\paren {p \lor q} \implies r} \implies \paren {\paren {p \implies r} \land \paren {q \implies r} } $
Line Pool Formula Rule Depends upon Notes
1 1 $\paren {p \lor q} \implies r$ Assumption (None)
2 1 $\paren {p \implies r} \land \paren {q \implies r}$ Sequent Introduction 1 Proof by Cases: Formulation 1: Reverse Implication
3 $\paren {\paren {p \lor q} \implies r} \implies \paren {\paren {p \implies r} \land \paren {q \implies r} }$ Rule of Implication: $\implies \II$ 1 – 2 Assumption 1 has been discharged